2003
DOI: 10.1051/kmae:2003036
|View full text |Cite
|
Sign up to set email alerts
|

Article

Abstract: SUMMARYThe eel population of the Camargue lagoon system can be divided into two subunits living in two distinct biotopes (freshwater and brackish water) and characterised by different population structures and especially growth patterns. The sub-population living in the Fumemorte canal (average salinity: 0.9 g/l) is a freshwater population type (81.6% females, maximum ages observed = 9 -11 years, slow growth (annual gain 46 mm)) whereas that of the Vaccarès lagoon (average salinity: 9.7 g/l over the same perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…As far as IG is concerned our findings with regard to yellow and silver eels from Göksu Delta further support Marchelidon et al (1999) and Acou et al (2003) who have reported a threshold value of ≥ 1.4% for gonado-somatic index characterizing the silvering stage.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…As far as IG is concerned our findings with regard to yellow and silver eels from Göksu Delta further support Marchelidon et al (1999) and Acou et al (2003) who have reported a threshold value of ≥ 1.4% for gonado-somatic index characterizing the silvering stage.…”
Section: Resultssupporting
confidence: 85%
“…Lefebvre et al (2003) have reported significant differences in size (length) of female silver eels even from two sites in the same delta (Rhone Delta). Likewise, Acou et al (2003) underline that the ovarian development which is characteristic of metamorphosis to silver stage occur at very variable body lengths varying between 400 and more than 750 mm. Nevertheless; mean body length of migrating female silver eels from Göksu Delta (72.90 ±4.88 cm) is consistent with classification made by Durif et al (2005) and Durif et al (2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations